Exploring Common Expectations from Students in Large Multilevel Secondary Level English Classes - Khati, Ashok Raj (Journal of NELTA, 2011)
English has been used in diverse contexts around the globe. Teaching English in large multilevel classes is one of the major challenges in ELT setting. The majority of classrooms consist of multilevel groups where students have different needs and learning styles. This type of heterogeneity may enrich the variety of social interaction, more life experiences and knowledge, more opinions, interests and ideas but it also creates situations that challenge teachers’ resourcefulness while trying to give each student an opportunity to learn English language. The situation is more challenging in under-resourced situations of Nepal. Moreover, in this type of classes teacher may not be familiar with different needs and prospects of students. Thus, this study attempts to find out the very common expectations of students in a large English class where students have different levels. Key words: Large class; Multilevel; Heterogeneous; Homogeneous; Mixed ability classes Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 98-105 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4614